Investimentos internacionais e a contrapartida social - Pereira, Tiago de Aguiar (2007)
Verifying that the volume of international investments and the roll of the new social players of international law, that is, the private corporations which invest in several different countries of the world, and, analyzing that the State can no longer by itself protect and achieve the fundamental human rights, more so in the new world context, where new rights become part of the fundamental rights, such as the right to development and the right to technology, it is now clear the necessity to engage the private sector into the search and promotion of human rights. This work will disclose the reasons, how and in what sense the private sector may be obliged to positive participate in this new journey